2019
DOI: 10.1186/s12944-019-1179-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological importance of bile cholesterol reabsorption: hepatic NPC1L1-exacerbated steatosis and decreasing VLDL-TG secretion in mice fed a high-fat diet

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases worldwide, although its pathogenesis remains to be elucidated. A recent study revealed that hepatic Niemann-Pick C1-Like 1 (NPC1L1), a cholesterol re-absorber from bile to the liver expressed on the bile canalicular membrane, is an exacerbation factor of NAFLD. Indeed, transgenic mice with hepatic expression of human NPC1L1 under a liver-specific promoter (L1-Tg mice) developed steatosis with a high-fat diet (HFD) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…NPC1L1 is also expressed in the human liver and facilitates cholesterol reuptake from bile to hepatocytes[ 67 ]. Further experiments suggested that NPC1L1 may be associated with impaired VLDL-TG secretion and subsequent TG hepatic accumulation[ 68 ]. NPC1L1 inhibition by ezetimibe ameliorated hepatic steatosis in genetically engineered L1-Tg mice characterized by enhanced hepatic NPC1L1 expression[ 69 , 70 ].…”
Section: Ezetimibementioning
confidence: 99%
“…NPC1L1 is also expressed in the human liver and facilitates cholesterol reuptake from bile to hepatocytes[ 67 ]. Further experiments suggested that NPC1L1 may be associated with impaired VLDL-TG secretion and subsequent TG hepatic accumulation[ 68 ]. NPC1L1 inhibition by ezetimibe ameliorated hepatic steatosis in genetically engineered L1-Tg mice characterized by enhanced hepatic NPC1L1 expression[ 69 , 70 ].…”
Section: Ezetimibementioning
confidence: 99%
“…NPC1L1, which reabsorbs cholesterol from bile and transports it to the liver, is expressed on the bile duct membrane and is an aggravating factor of NAFLD ( 120 ). NAFLD often exhibits oxidative stress, which leads to increased free-radical activity and lipid peroxidation by increasing reactive oxygen species (ROS).…”
Section: Bile Acid Metabolism In Nafldmentioning
confidence: 99%
“…The liver is a critical organ for cholesterol synthesis and excretion to the intestinal lumen; however, around 95% of cholesterol excretion via hepatobiliary cholesterol excretion is absorbed by the intestine [ 9 ]. Previous studies have shown that routes for cholesterol secretion via hepatobiliary transport and trans-intestinal cholesterol secretion or excretion (TICE), which are direct transport pathways through intestinal enterocytes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%